Programmable finite automata for VLSI - Culik, K.; Jürgensen, H. (International journal of computer mathematics, 1983)
We describe a method VLSI for design of programmable finite automata. For any fixed k it can be programmed to deterministically simulate a non-deterministic finite auto- maton with at most k states. For some constant c it runs in time on inputs of length n>b and in time on inputs of length n≧b where b is a constant influencing the size of the realisation, which can be chosen so that ck is much smaller than b. The design is modular, it consists of 0(bk 2 ) identical processes connected in a uniform manner.